2021
DOI: 10.3390/cells10030648
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Cancer Gene Expression Signatures: Current Status and Challenges

Abstract: Current staging systems of cancer are mainly based on the anatomical extent of disease. They need refinement by biological parameters to improve stratification of patients for tumor therapy or surveillance strategies. Thanks to developments in genomic, transcriptomic, and big-data technologies, we are now able to explore molecular characteristics of tumors in detail and determine their clinical relevance. This has led to numerous prognostic and predictive gene expression signatures that have the potential to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 117 publications
0
75
0
2
Order By: Relevance
“… 9 , 10 These classification systems are currently limited in clinical practice due to a lack of standardization and the requirement of bioinformatics resources. 11 An immunohistochemistry-based scoring approach used to assess the recurrence risk, termed Immunoscore®, has been established and validated, which measures the tumor core and invasive margin of CD3+ and CD8+ T cells. 12 Although Immunoscore® exhibits stable power in assessing the recurrence risk of early-stage CRC, its performance remains moderately accurate according to the C-index evaluation in an international trial.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 These classification systems are currently limited in clinical practice due to a lack of standardization and the requirement of bioinformatics resources. 11 An immunohistochemistry-based scoring approach used to assess the recurrence risk, termed Immunoscore®, has been established and validated, which measures the tumor core and invasive margin of CD3+ and CD8+ T cells. 12 Although Immunoscore® exhibits stable power in assessing the recurrence risk of early-stage CRC, its performance remains moderately accurate according to the C-index evaluation in an international trial.…”
Section: Introductionmentioning
confidence: 99%
“…38 A recent review also arise the concern about the gene signatures that lack reproducibility and cannot enter clinical applications. 39 Although state-of-the-art bioinformatics tools have been extensively applied to HCC to mine biomarkers, current analysis pipelines still focus on hub genes, ignoring the module-level information. 40,41 We also observed that hub genes/signature genes are not so reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Switch genes were enriched within the top 10 genes in each module (Hypergeometric test P < 0.01). They were SNAPC4, AXL, HNF1A, HNF4A, NCAPG, XAB2, TARS2, MED27, TAOK2, CD2BP2, ZNF768, (39) Factor: EHF (3E-6), ELK-1 (4E-6) PUF60 S3). MIENTURNET tool identified that these switch genes may be regulated by miR-98-5p (P = 0.02) and miR-484 (P = 0.03).…”
Section: Differentially Expressed Modules (Dem) In Hcc Developmentmentioning
confidence: 99%
“…Hu and other researchers used the NMF algorithm with the rank value set to 3 to classify patients with CRC, but they did not compare the differences in different typing methods when the rank value was at 2, 3, and 5 respectively. Some scholars [32][33][34][35][36][37][38][39][40] built risk models to predict the survival of patients with CRC, but no one compared the accuracy of their respective models.…”
Section: Discussionmentioning
confidence: 99%